Ibrutinib directly reduces CD8+T cell exhaustion independent of BTK - Li, Ling; Zhao, Manzhi; Kiernan, Caoimhe H.; Castro Eiro, Melisa D.; van Meurs, Marjan; Brouwers-Haspels, Inge; Wilmsen, Merel E. P.; Grashof, Dwin G. B.; van de Werken, Harmen J. G.; Hendriks, Rudi W.; Mueller, Yvonne M.; Katsikis, Peter D. (Frontiers in Immunology, 2023)
Cytotoxic CD8+ T cell (CTL) exhaustion is a dysfunctional state of T cells triggered by persistent antigen stimulation, with the characteristics of increased inhibitory receptors, impaired cytokine production and a distinct transcriptional profile. Evidence from immune checkpoint blockade therapy supports that reversing T cell exhaustion is a promising strategy in cancer treatment. Ibrutinib, is a potent inhibitor of BTK, which has been approved for the treatment of chronic lymphocytic leukemia. Previous studies have reported improved function of T cells in ibrutinib long-term treated patients but the mechanism remains unclear. We investigated whether ibrutinib directly acts on CD8+ T cells and reinvigorates exhausted CTLs. By using an established in vitro CTL exhaustion system, we show that ibrutinib reduces exhaustion-related features of exhausted CTLs. These changes included decreased inhibitory receptor expression, enhanced cytokine production, and downregulation of the transcription factor TOX with upregulation of TCF1. RNA-seq revealed that ibrutinib directly reduced the exhaustion-related transcriptional profile of these cells. Importantly, using btk deficient mice we show the effect of ibrutinib is independent of BTK expression, and therefore mediated by one of its other targets. To conclude, our study demonstrates that ibrutinib directly ameliorates CTL exhaustion, and provides evidence for its synergistic use with cancer immunotherapy.